The role of aggregators in facilitating industrial demand response: Evidence from Germany - Jan Stede; Karin Arnold; Christa Dufter; Georg Holtz; Serafin von Roon; Jörn C. Richstein (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Industrial demand response can play an important part in balancing the intermittent production from a growing share of renewable energies in electricity markets. This paper analyses the role of aggregators - intermediaries between participants and the electricity market - in facilitating industrial demand response. Based on the results from semi-structured interviews with German demand response aggregators, as well as a wider stakeholder online survey, we examine the role of aggregators in overcoming barriers to industrial demand response. We find that a central role for aggregators is to raise awareness for the potentials of demand response, as well as to support implementation by engaging key actors in industrial companies. Moreover, we develop a taxonomy that helps analyse how the different functional roles of aggregators create economic value. We find that there is considerable heterogeneity in the kind of services that aggregators offer, many of which do create significant economic value. However, some of the functional roles that aggregators currently fill may become obsolete once market barriers to demand response are reduced or knowledge on demand response becomes more diffused.
Keywords: D22; L23; Q40; Q41; 330; aggregator; demand response; barriers; function; roles; industry; interview